(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Relevance. Age-related macular degeneration (AMD) and glaucoma are currently the main causes of irreversible vision loss in developed countries. Purpose. To study the epidemiological and clinical-functional aspects of the combined course of age-related macular degeneration and primary glaucoma and to assess the quality of life of these patients. Material and Methods. The analysis of 5,000 outpatient records of patients over 35 years of age who were observed in the consultative polyclinic of the multidisciplinary clinic of the Tashkent Medical Academy in the period 2011-2022 was carried out. All patients were divided into three groups: group 1 - glaucoma, group 2 - AMD, group 3 - glaucoma + AMD. Results. A retrospective analysis of 5,000 outpatient records of patients older than 35 years revealed the presence of glaucoma in 30.3% of cases, AMD - in 37.94%, their combination - in 20.3%. At the same time, in the structure of AMD, signs of the dry form of the disease were diagnosed in 74% of cases, geographical atrophy - in 12% and wet form - in 14%. However, it requires careful monitoring of the dynamics of visual-functional and structural changes in the retina and optic nerve, as well as timely correction of therapy. Conclusion. The combined course of diseases having a neurodegenerative nature of the lesion leads to a decrease in not only visual, but also cognitive functions, significantly affects the quality of life of patients of the older age group and their adaptation in society.